RELATIONSHIP BETWEEN PERFORMANCE IN SECONDARY SCHOOL MATHEMATICS AND DIPLOMA’S STRUCTURED PROGRAMMING UNIT IN TECHNICAL INSTITUTES WITHIN MERU COUNTY, KENYA - M’Lingera, Meeme, Julius; Kathuri, Prof. Nephat Justus; Marete, Jacob Bundi (IJRDO- Journal of Educational Research, 2017)
The poor performance in structured programming unit in Kenya national examinations council (KNEC) examination for diploma in Information Communication Technology (DICT) programme by students in module one has caused a great outcry in most of the Technical Institutes in Kenya. The purpose of this study was to determine the relationship between the students’ performance in secondary school mathematics and diploma’s structured programming unit in technical institutes within Meru County, Kenya. The target population composed of all the 118 students that had sat for the KNEC examination in structured programming unit from the year 2012 to 2015 in Meru, Kiirua and Nkabune technical institutes, and the six lecturers that had taught them in the structured programming unit. The study established that there is no significant relationship between the students’ performance in secondary school mathematics and diploma’s structured programming unit in technical institutes within Meru County, Kenya ( r = 0.098, p = 0.291, α = 0.05, R2 = 0.010, adjusted R2 = 0.001, f = 1.124).